Simultaneous Detection of Both GDNF and GFRα1 Expression Patterns in the Mouse Central Nervous System - Ortega-de San Luis, Clara; Pascual, Alberto (Frontiers in Neuroanatomy, 2016)
Glial cell line-derived neurotrophic factor (GDNF) is proposed as a therapeutic tool in Parkinson’s disease, addiction-related disorders, and neurodegenerative conditions affecting motor neurons. Despite the high amount of work about GDNF therapeutic application, the neuronal circuits requiring GDNF trophic support in the brain and spinal cord are poorly characterized. Here, we defined GDNF and GDNF family receptor-α 1 (GFRα1) expression pattern in the brain and spinal cord of newborn and adult mice. We performed systematic and simultaneous detection of EGFP and LacZ expressing alleles in reporter mice and asked whether modifications of this signaling pathway lead to a significant central nervous system (CNS) alteration. GFRα1 was predominantly expressed by neurons but also by an unexpected population of non-neuronal cells. GFRα1 expression pattern was wider in neonatal than in adult CNS and GDNF expression was restricted in comparison with GFRα1 at both developmental time points. The use of confocal microscopy to imaging X-gal deposits and EGFP allowed us to identify regions containing cells that expressed both proteins and to discriminate between auto and non-autotrophic signaling. We also suggested long-range GDNF-GFRα1 circuits taking advantage of the ability of the EGFP genetically encoded reporter to label long distance projecting axons. The complete elimination of either the ligand or the receptor during development did not produce major abnormalities, suggesting a preponderant role for GDNF signaling during adulthood. In the spinal cord, our results pointed to local modulatory interneurons as the main target of GDNF produced by Clarke’s column cells. Our work increases the understanding on how GDNF signals in the CNS and establish a crucial framework for posterior studies addressing either the biological role of GDNF or the optimization of trophic factor-based therapies.